A NEEDS ANALYSIS OF BIG BOOK INTEGRATING GOOD HEALTH AND WELL-BEING AS READING MEDIA FOR SHARED READING ACTIVITIES IN FACILITATING PRESCHOOL STUDENTS’ READING ENGAGEMENT - I Putu Andika Putra; Ni Wayan Surya Mahayanti; Ni Luh Putu Era Adnyayanti (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
Early literacy development plays a crucial role in shaping children’s academic readiness and long-term learning success. However, limited availability of visually accessible and contextually meaningful reading materials may reduce preschool students’ reading engagement during shared reading activities. This study aimed to analyze the needs of teachers and preschool students regarding the use of Big Books integrating SDG 3 (Good Health and Well-Being) to support reading engagement. A qualitative descriptive design was employed at one of the Kindergarten in Singaraja, involving classroom observation and a semi-structured interview with the teacher. The findings revealed three primary needs: large-format and visually clear books, narrative-based integration of health themes, and interactive features to sustain students’ engagement. The study concludes that developing SDG 3–integrated Big Books is pedagogically necessary to enhance shared reading practices and foster preschool students’ reading engagement. ABSTRAK Perkembangan literasi awal memegang peranan yang sangat penting dalam membentuk kesiapan akademik anak serta keberhasilan belajar jangka panjang. Namun, keterbatasan ketersediaan bahan bacaan yang mudah diakses secara visual dan bermakna secara kontekstual dapat mengurangi keterlibatan membaca siswa prasekolah selama kegiatan membaca bersama (shared reading). Penelitian ini bertujuan untuk menganalisis kebutuhan guru dan siswa prasekolah terkait penggunaan Big Book yang mengintegrasikan SDG 3 (Good Health and Well-Being) untuk mendukung keterlibatan membaca. Penelitian ini menggunakan desain deskriptif kualitatif yang dilaksanakan di salah satu taman kanak-kanak di Singaraja, dengan melibatkan observasi kelas dan wawancara semi-terstruktur dengan guru. Temuan penelitian menunjukkan tiga kebutuhan utama, yaitu buku berukuran besar dengan tampilan visual yang jelas, integrasi tema kesehatan berbasis naratif, serta fitur interaktif untuk mempertahankan keterlibatan siswa. Penelitian ini menyimpulkan bahwa pengembangan Big Book yang terintegrasi dengan SDG 3 secara pedagogis diperlukan untuk meningkatkan praktik shared reading dan menumbuhkan keterlibatan membaca siswa prasekolah.